Imaging Calcium in Hippocampal Presynaptic Terminals With a Ratiometric Calcium Sensor in a Novel Transgenic Mouse - Al-Osta, Ibrahim; Mucha, Mariusz; Pereda, Daniel; Piqué-Gili, Marta; Okorocha, Albert E.; Thomas, Roisin; Hartell, Nicholas A. (Frontiers in Cellular Neuroscience, 2018)
Genetically encoded calcium indicators have gained widespread use for measurement of neuronal activity but their low expression levels in transgenic mice tend to limit sensitivity. We have developed a transgenic mouse line (SyG37) that expresses a ratiometric calcium sensor, SyGCaMP2-mCherry, that is expressed throughout the brain but targeted to presynaptic terminals. Within the CA1 and CA3 regions of hippocampus of male and female mice, SyGaMP2 fluorescence responds linearly up to 10 electrical stimuli at frequencies up to 100 Hz and it can detect responses to a single stimulus. Responses in single boutons can be measured using multiphoton microscopy. The ensemble amplitude of SyGCaMP2 responses is a function of the number of stimuli applied and the number of contributing boutons. The peak responses and initial rates of calcium influx in single boutons in CA1 and CA3 were similar but the rate of calcium clearance from CA3 boutons after stimulation was significantly faster. In CA1, DNQX reduced SyGCaMP2 responses to Schaffer collateral stimulation to 86% of baseline indicating that 14% of the total response originated from presynaptic terminals of neurones synaptically driven via AMPA receptors. Theta burst stimulation induced LTP of both SyGCaMP2 and fEPSP responses in both young and 18-month-old mice. The proportion of postsynaptically connected terminals increased significantly to 76% of the total after LTP induction. The SyG37 mouse allows stable optical detection of synaptic activation and connectivity at the single bouton level and can be used to characterise the contributions of presynaptic calcium to synaptic transmission and plasticity.